2022
DOI: 10.1016/j.envres.2021.111948
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to fine particulate matter air pollution: An ecological study of its effect on COVID-19 cases and fatality in Germany

Abstract: Background COVID-19 is a lung disease, and there is medical evidence that air pollution is one of the external causes of lung diseases. Fine particulate matter is one of the air pollutants that damages pulmonary tissue. The combination of the coronavirus and fine particulate matter air pollution may exacerbate the coronavirus’ effect on human health. Research question This paper considers whether the long-term concentration of fine particulate matter of different sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 65 publications
0
27
1
3
Order By: Relevance
“…Excessive free radicals weaken the cellular antioxidant capacity, leading to lipid peroxidation and increased intracellular calcium concentrations, further inducing cellular damage (Xing et al 2016). Finally, SARS-CoV-2 enters the cell through binding to the angiotensin-converting enzyme 2 (ACE2) receptor, and this process can be enhanced by PM exposure (Tung et al 2021). The binding of SARS-CoV-2 and the ACE2 receptor resulted in the downregulation of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive free radicals weaken the cellular antioxidant capacity, leading to lipid peroxidation and increased intracellular calcium concentrations, further inducing cellular damage (Xing et al 2016). Finally, SARS-CoV-2 enters the cell through binding to the angiotensin-converting enzyme 2 (ACE2) receptor, and this process can be enhanced by PM exposure (Tung et al 2021). The binding of SARS-CoV-2 and the ACE2 receptor resulted in the downregulation of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a multicity study in China found that for each 10 μg/m 3 increase in PM 10 and PM 2.5 , the risk of COVID-19 increased by 5% and 6%, respectively ( Wang et al 2020 ). Another study in Germany showed that every 1 μg/m 3 increase in PM 10 and PM 2.5 was associated with 52.38 and 199.46 more confirmed COVID-19 cases per 100,000 inhabitants, respectively ( Prinz and Richter 2022 ). The associations between ambient PM exposure and the risk of COVID-19 have been ardently discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter -PM in different size fractions (PM1 μm, PM2.5 μm, and PM10 μm) and gaseous air pollutants (ozone-O 3 , nitrogen dioxide-NO 2 , sulfur dioxide-SO 2 , carbon monoxide-CO) may have an important impact on COVID-19 disease transmission ( Marquès and Domingo, 2021 , 2022 ; Marquès et al, 2022 ; Zoran et al, 2021 , 2022 ; Domingo et al, 2020 ; López-Feldman et al, 2021 ). Due to their increased oxidative toxicity, epidemiologic studies have shown a connection between outdoor ( Shao et al, 2022 ; Xu et al, 2022 ; Ho et al, 2021 ; Bakadia et al, 2021 ; Cao et al, 2021 ; Copat et al, 2020 ; Mu et al, 2021 ; Rahimi et al, 2021 ) acute and chronic exposure ( Wang et al, 2022 ) to high levels of air pollutants in large urban areas, that are responsible for respiratory and cardiovascular morbidity and higher mortality rates ( Hvidtfeldt et al, 2021 ; Domingo and Rovira, 2020 ; Leirião et al, 2022 ; Prinz and Richter, 2022 ; Khan et al, 2019 ; Travaglio et al, 2021 ). Was demonstrated that long-term exposure to particulate matter PM10 concentrations above WHO guidelines implemented by the Directive 2008/50/EU and the US-EPA, exacerbate COVID-19 health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There were mixed views regarding whether particulate matter in air facilitates spread of infectious disease(s) like COVID-19, whether the combination of respiratory disease and air pollution is a risk factor for more severe symptoms and prognosis of COVID-19, or whether pandemic-related societal restrictions led to improved air quality. The lack of agreement on these issues parallels results from current assessments of the literature ( Adam et al, 2021 ; Marquès and Domingo, 2022 ; Prinz and Richter, 2022 ; Ram et al, 2021 ).…”
Section: Resultsmentioning
confidence: 77%